Efficiency of talcum-biochars in immobilization of heavy metals and promotion of the growth of Brassica chinensis in contaminated agricultural soil - Hao-Hao Lyu; Kai Cheng; Li-Li He; Sheng-Mao Yang; Yu-Xue Liu; Ling-Cong You; Yu-Ying Wang (Plant Stress)
Soil contamination with multiple heavy metals poses a significant threat to the global environment. This study aimed to evaluate the ability of a novel talcum-modified biochar as a soil amendment to improve soil properties and remediation performance in agricultural soils contaminated with various heavy metals. Pot experiments were performed in a greenhouse to evaluate the influences of biochar and talcum-modified biochars at 0 %, 0.5 %, 1 %, and 2 % application rates on growth and heavy metal accumulation in Brassica chinensis (B. chinensis). The talcum-biochar composites exhibited superior immobilization efficacy for multiple heavy metals compared to pristine biochar. CaCl2-heavy metal contents decreased under the treatment with talcum-biochar, in contrast to the control. Sequential extraction procedures revealed that the more accessible forms of heavy metals were converted into less accessible forms. The application of talcum-biochar reduced the Cu, Zn, Cr, and Cd concentrations in B. chinensis, potentially due to a decrease in their bioavailability in the soil. Following the addition of talcum-biochar composites, increases in soil pH, available P and K levels, total N content, and organic matter concentrations were observed. Additionally, a significant enhancement in catalase and urease activities was noted, whereas acid phosphatase activity was inhibited. Therefore, the utilization of talcum-biochar composites as amendments has great potential for enhancing the soil environment and remediating multiple heavy metal-contaminated soils, making it an eco-friendly and cost-effective approach.